Revolusi al-Qu’ran Jamâl al-Bannâ sebagai Arah Baru Metodologi Studi Islam - Zamzami, Mukhammad (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2015)
Ontologically, Gamal al-Banna viewed that interpretation is the process to understand the Koran. Therefore he did the deconstruction of classical commentaries domination which is loaded with influences of the political uproar in the past Middle East. From such a deconstruction, he went to the reconstruction of the Koran within the concept of Tatwîr al-Qur’ân. There is a dimension of art that must be understood from the essence of Koran and should be permeated by all Muslims. For him, the Koran is an art book, and its largest or greatest miracle is language as a tool to understand the art found within it. The secret miracle rises from the musical reading of the Koran which could be a psychological approach, just by listening the reading. Through this stage of irfani, the Koran could be the media of human civilization revolution. In his concept, Gamal didn’t assert one method or restrict to a current science or method. He refused if one current method has a warranty as the only way to find the truth, because the Koran itself should not be restricted